Morphological Characters and Histology of Pheretima darnleiensis - ANDY DARMAWAN; RIKA RAFFIUDIN; TRI HERU WIDARTO (Bogor Agricultural University, Indonesia, 2012)
Pheretima darnleiensis is a native earthworm of Southeast Asia, India, and Japan. Although it is commonly found in Indonesia, the earthworm has never been studied well. This study was aimed to examine the morphological characters and structure of its several organs for an identification purpose, which is important for the earthworm culture. Earthworms were collected in a plot of 55-150 x 55-150 cm width and 20 cm depth at Bogor Agricultural University in Darmaga and Baranangsiang Campuses by hand sorting method. Examinations were carried out on its external as well as internal characters. The histology of the organs was studied using paraffin method. The observed characters on P. darnleiensis were the presence of prostate gland, one pair of male pores on segment XVIII, a cylindrical body with perichaetine setae, caeca on segment XXVII, copulatory pouches without diverticula and stalked glands, bithecal spermatheca with nephridia, and the first spermathecal pore on segment 4/5. In addition, other characters found on P. darnleiensis were the presence of an annular clitellum on segment XIV-XVI, an epilobus prostomium with open base, approximately 40 single pointed setae on segment XIII, one midventral female pore on segment XIV, one pair of lateroventral male pores on segment XVIII, four pairs of lateroventral spermathecal pores on segment 4/5, 5/6, 6/7, 7/8, and the first middorsal dorsal pore on segment 12/13. The histology of P. darnleiensis showed basic structure as found in other earthworms.